Melatonin Is Involved in Regulation of the Expression of Neural Cell Adhesion Molecules in the Rat Brain - Nedzvetsky, V. S.; Baydas, G.; Nerush, P. A.; Kirichenko, S. V. (Springer, 2002)
Cell adhesion molecules play a diverse role in neural development, signal transduction, structural linkage to extracellular and intracellular proteins, synaptic stabilization, neurogenesis, and learning. Neural cell adhesion molecules (NCAM) are members of the immunoglobulin superfamily and are involved in synaptic rearrangements in the mature brain. There are three major NCAM isoforms: NCAM 180, NCAM 140, and NCAM 120. Several studies reported that NCAM play a central role in memory formation. We investigated the effects of melatonin on the expression of NCAM in the hippocampus, cortex, and cerebellum of rats. The levels of NCAM isoforms were determined by Western blotting. After administration of melatonin for 7 days, expression of NCAM 180 increased both in the hippocampus and in the cortex, as compared with the control. In contrast, in rats exposed to constant illumination for 7 days (a procedure that inhibits endogenous production of melatonin), levels of NCAM 180 dropped in the hippocampus and became undetectable in the cortex and cerebellum. Levels of NCAM 140 in the hippocampus of light-exposed rats also decreased. There was no change in the expression of NCAM 120 in any brain region. This is the first report indicating that melatonin exerts a modulatory effect on the expression of NCAM in brain areas related to realization of cognitive functions. Melatonin may be involved in structural remodeling of synaptic connections during memory and learning processes.
Keywords: melatonin; neural cell adhesion molecule; constant light; memory